First report of triticale blast caused by the fungus Magnaporthe oryzae pathotype Triticum in Bangladesh. Issue 2 (4th March 2021) - Roy, Krishna Kanta; Muzahid-E-Rahman,; Reza, Mostofa Ali; Mustarin, Kishowar E; Malaker, Paritosh Kumar; Barma, Naresh Chandra Deb; Hossain, Israil; He, Xinyao; Singh, Pawan Kumar
Abstract: Symptoms of partially bleached and completely white heads were observed in a triticale (× Triticosecale ) cultivar 'BARI Triticale 1ʹ in the research plots at the Regional Agricultural Research Station, Jashore, Bangladesh, during April 2019. Foliar symptoms with elliptical or eye-shaped lesions were also found on plant leaves. The main intention of this study was to isolate and identify the causal organism of the disease. Morphological characteristics of the pathogen showed the presence of pyriform 2-septate hyaline conidia and coloured conidiophores, indicating the presence of the fungus Magnaporthe oryzae . Molecular analyses by ITS sequence analysis and amplification of the product with MoT3 primers confirmed the identity of the fungus as M. oryzae pathotype Triticum . The pathogenicity of the representative isolates was confirmed by inoculation of triticale heads and leaves under laboratory conditions, resulting in similar symptoms as observed in the field. To our knowledge, this is the first report of triticale blast caused by M. oryzae pathotype Triticum in Bangladesh.